Territorial Dynamics in Small-Scale Fishing Villages: Economics, Experiences and Conflicts. The Case of Guabún and Puñihuil in the Ancud District, Chiloé - Francisco Ther Ríos; Jaime Valderrama Bravo (CUHSO)
The socio-economic and environmental transformations undergoneby fishing villages, as a result of the premature insertion of this sectorinto the international economy, come in addition to a variety of modernisationprocesses affecting the societies which inhabit coastal spaces, changingtheir daily lives. A second factor is the growing supply of tourism servicesalong the coast, implying new adaptations for fishing settlements. Thesefactors act on the coastline, generating processes of disadaptation and disorientationin fishing communities. This constitutes a negative factor bothfor territorial ordering and for the administration of the resources on whichsmall-scale fishing depends. In this context, the article examines in greaterdepth the territorial dynamics present in two coastal communities on ChiloéIsland, through analysis of the economic and cultural processes and thevariations over time of the fishing grounds used by small-scale fishermen.A qualitative methodology is used, based on participative cartography andin-depth interviews, as well as a bio-economic survey. The central objectiveis to understand from a geosocial focus the economic and productive processesin the two villages, together with possible causes of conflict. Finally,we present the basic factors and aspirations which have made the two communitiesa focus of attention in the ambit of local development in this typeof productive activity.